Penerapan model pembelajaran problem based learning untuk meningkatkan keaktifan dan prestasi belajar IPS - Niken Purwaningtyas (Journal of diversity in learning (JDIL), 2023)
The purpose of this study was to find out whether the application of the Problem Based Learning learning model had an effect on increasing the social studies activity and achievement in class VII students of SMP Negeri I Glagah. The results showed that using the Problem Based Learning learning model had a positive impact on increasing activity and achievement. learning Social Sciences (IPS) in class VII students of SMP Negeri 2 Lamongan. Cycles 1 and 2 of the learning outcomes obtained by students show that cycle 1 can be seen that classically the learning completeness has increased, namely 68.75%, compared to the learning outcomes before the cycle, but still has not reached the specified classical completeness, which is 85% and the average value is 78 ,41. Cycle 2 can be seen that classically the learning completeness has been achieved because it is more than 85%, namely 87.50% and the average value is 82.91. Problem-based learning model, gradually students are able to increase their activeness in discussions and improve their problem-solving skills.